2019
DOI: 10.1021/acs.jafc.8b06479
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Borax Cross-Linked Starch Nanoparticles for Improvement of Mechanical Properties of Maize Starch Films

Abstract: Recently, starch nanoparticles have attracted widespread attention from various fields. In this study, a new strategy for preparing covalent-cross-linked starch nanoparticles was developed using boron ester bonds formed between debranched starch (DBS) and borax. The nanoparticles were characterized by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), X-ray diffraction (XRD), dynamic light scattering (DLS), differential scanning calorimeter (DSC), and thermogravimetric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 38 publications
2
30
0
2
Order By: Relevance
“…The factor that most strongly impacts the physical properties of starch films is the amylose to amylopectin ratio. Most starches are predominantly amylopectin (waxy corn starch can be up to 100% amylopectin) although some sources, such as high amylose corn starch, can have upward of 70% amylose (Lu et al, 2019). In general, it has been observed that higher percentages of amylose lead to more rigid films as denoted by a higher TS and EM and a simultaneous decrease in EAB as a result of an increased crystallinity (Cano, Jimenez, Chafer, Gonzalez, Dilute alkaline steeping (Gani et al, 2017;Van Hung et al, 2016;Ziegler et al, 2017) Potato 390 Mt Wet milling (Bergthaller, 2004;Bertoft & Blennow, 2016;Nawaz et al, 2020;Singh et al, 2018) Cassava root (Gous & Fox, 2017;Rittenauer, Kolesnik, Gastl, & Becker, 2016;You & Izydorczyk, 2002;Yu et al, 2017) Oat (Chu, 2014;Xu et al, 2017) Sago >90 kt Milling followed by wet sieving (Arshad, Zaman, Rawi, & Sarbini, 2018;Ehara, Toyoda, & Johnson, 2018;Karim, Tie, Manan, & Zaidul, 2008;Naseri et al, 2019) Note: Estimated yearly production in Indonesia, the largest producer of sago.…”
Section: The Complexities Of Starch and Starch Film Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The factor that most strongly impacts the physical properties of starch films is the amylose to amylopectin ratio. Most starches are predominantly amylopectin (waxy corn starch can be up to 100% amylopectin) although some sources, such as high amylose corn starch, can have upward of 70% amylose (Lu et al, 2019). In general, it has been observed that higher percentages of amylose lead to more rigid films as denoted by a higher TS and EM and a simultaneous decrease in EAB as a result of an increased crystallinity (Cano, Jimenez, Chafer, Gonzalez, Dilute alkaline steeping (Gani et al, 2017;Van Hung et al, 2016;Ziegler et al, 2017) Potato 390 Mt Wet milling (Bergthaller, 2004;Bertoft & Blennow, 2016;Nawaz et al, 2020;Singh et al, 2018) Cassava root (Gous & Fox, 2017;Rittenauer, Kolesnik, Gastl, & Becker, 2016;You & Izydorczyk, 2002;Yu et al, 2017) Oat (Chu, 2014;Xu et al, 2017) Sago >90 kt Milling followed by wet sieving (Arshad, Zaman, Rawi, & Sarbini, 2018;Ehara, Toyoda, & Johnson, 2018;Karim, Tie, Manan, & Zaidul, 2008;Naseri et al, 2019) Note: Estimated yearly production in Indonesia, the largest producer of sago.…”
Section: The Complexities Of Starch and Starch Film Processingmentioning
confidence: 99%
“…Most notably, starch nanocrystals or starch NPs act as reinforcing agents to generate nanocomposites with improved TS, EM, and WVP. Starch NPs generated by debranching and crosslinking waxy corn starch (Table 2, entry 5) were dispersed in corn starch and were found to be effective at slightly improving EAB (Lu et al, 2019), whereas incorporation of starch nanocrystals into an oxidized cassava network (Table 2, entry 19) led to significantly decreased EAB (Dai, Zhang, & Cheng, 2020). Fang et al (2020) synthesized NPs from waxy corn starch and κ-carrageenan to endow starch films with antimicrobial properties while improving the mechanical properties of hydroxypropyl cassava starch films (Table 2, entry 18).…”
Section: Starch As An Additivementioning
confidence: 99%
See 1 more Smart Citation
“…Starch is a kind of renewable, inexpensive, environmentally friendly, and abundantly available polymer material, but its application has been limited by its high hydroscopicity and brittleness . Other the hand, biodegradable aliphatic polyester (such as polylactic acid (PLA) and polycaprolactone (PCL)) is hydrophobic, with good mechanical properties but great expense.…”
Section: Introductionmentioning
confidence: 99%
“…Entre os polímeros de fontes renováveis, o amido tem sido considerado como um dos materiais mais promissores em substituição aos polímeros sintéticos em razão da sua grande disponibilidade, biodegradabilidade e baixo custo. Apesar de vantajosos quanto ao custo e apelo ambiental, os filmes de amido são suscetíveis ao ataque de umidade, devido a sua característica hidrofílica, resultando em alterações na estabilidade dimensional e propriedades mecânicas [5,6]. A utilização de modificações químicas ou físicas, além do uso de aditivos e/ou plastificantes é uma alternativa para modular as propriedades de filmes de amido e amplia as aplicações deste material [7,8,9].…”
Section: Introductionunclassified